Studi Model Tungku Pembakaran Untuk Pembuatan Patung Keramik Monumental - Marwanto, Aries Budi (Institut Seni Indoensia Surakarta, 2010)
In the process of creating works of ceramic art, the amount of size is a problem. When making large ceramic works, meaning the risk of failure too great. This relates very well with the chemical composition of clay and mixtures that fit. After that also the longer the drying process, whereas the longer period of drying, the longer the duration also susceptible crack or rupture. Last is the burning issue that must use a large fireplace as well. Larger furnace means also more expensive. Some of these constraints which ultimately makes ceramic artists in Indonesia do not dare to make the work of a great experiment.Complex process coupled with the limited equipment furnace (oven) because high-priced, making leaps of idea creation Indonesian ceramic artist does not as dynamic as the other branches of art. Especially in terms of its magnitude. Noted, functional ceramic wares produced at large is only 2 meters, which is in Plered West Java, while the ceramic art ever created by Dadang Christanto very monumental in his work